Volume-accumulated reflectivity of the outer retina (integral) on spectral domain optical coherence tomography as a predictor of cone cell density: a pilot study - Li, Wenting; Chen, Wenwen; Zhou, Xiyue; Jiang, Tingting; Zhang, Juan; Wang, Min; Wu, Jihong; Gu, Junxiang; Chang, Qing (BMC ophthalmology, 2023)
The study aims to investigate the relationship between the volume-accumulated reflectivity (termed "integral") on spectral domain optical coherence tomography (SD-OCT) and cone density on adaptive optics (AO) imaging. In this cross-sectional study, both eyes of 32 healthy subjects and 5 patients with inherited retinal diseases (IRD) were studied. The parameter, integral, was defined as the volume-accumulated reflectivity values in a selected region on OCT images; integrals of the ellipsoid zone (EZ) and interdigitation zone (IZ) were measured at 2°, 3°, 4°, 5°and 6° eccentricity along the four meridians on fovea-centered OCT B-scans. Cone density in the same region was measured using a flood illumination adaptive optics camera RTX1. Integrals of EZ, IZ and cone density shared similar distribution patterns. Integral of the IZ was better correlated with cone density in both healthy people (r = 0.968, p < 0.001) and those with IRD (r = 0.823, p < 0.001) than direct measurements of reflectivity on OCT images. A strong correlation was found between best corrected visual acuity (BCVA) and cone density at 2° eccentricity (r = -0.857, p = 0.002). BCVA was also correlated with the integral of the IZ at the foveola (r = -0.746, p = 0.013) and fovea (r = -0.822, p = 0.004). The new parameter "integral" of the photoreceptor outer segment measured from SD-OCT was noted to correlate with cone density and visual function in this pilot study.